Participation of Women in Fisheries: A Study on Gender Issues in Manipur, India - Meetei, Waikhom Tomthinnganba; Saha, Biswarup; Pal, Prasenjit (International Journal of Bio-resource and Stress Management, 2023)
Conscious efforts to address the gender issues in fisheries sector and the involvement of more women through explicit support to their participation are yet to be undertaken intensively in North Eastern region of India. Therefore, the study was conducted to know the level of participation of women in fisheries activities in Manipur and to identify the different constraints perceived by them while participating in fisheries activities. One hundred and twenty women who were involved in different fisheries activities formed the sample of the study. A semi-structured interview schedule was used to collect the information through personal interview. The data was analyzed by using frequency, percentage, ‘Z’ test. Empowerment index was also developed for the study to know the level of empowerment after participation in fisheries activities. The participation of women was found maximum in aspects of capture fisheries, followed by post harvesting, marketing of fishes and stocking of fish seeds. Most significant participation under the post harvesting practices was value addition (3.40), cleaning and grading (3.40) and transporting (2.93). The ‘Z’ values revealed that, there was significant difference in index values of empowerment of rural women before and after taking up fisheries activity, which clearly revealed the fact that participation in fisheries activity significantly contributed for enhancement in empowerment. Lack of access and control over resources (1.80), low access to credit (1.74), lack of confident in technical issues (1.60), lack of women friendly aquaculture technology (1.50) were the major constraints identified in empowerment of women through participation in fisheries activities.